2023
DOI: 10.3390/ijms24065907
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation in Mice Resulted in Abnormal Placentation through Its Effects on Proliferation and Cytokine Production of Uterine NK Cells

Abstract: Ovarian stimulation is associated with an increased incidence of abnormal placentation. Uterine natural killer (uNK) cells are the major subpopulation of decidual immune cells, which are crucial for placentation. In a previous study, we found that ovarian stimulation impairs uNK cell density on gestation day (GD) 8.5 in mice. However, it was not clear how ovarian stimulation led to a reduction in the density of uNK cells. In this study, we constructed two mouse models, an in vitro mouse embryo transfer model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In terms of uNK cell recruitment, Chantakru, S, demonstrated that estrogen could enhance homing (ovariectomized C57Bl/6 mice, 17β-estradiol at 100 ng/day, 3 days) by upregulating the expression of L-selectin and α-integrin on circulatory CD56 bright NK cells [ 47 ]. Conversely, Ma, R et al found that estrogen stimulation (pseudopregnant CD1 mice obtained blastocysts transfer, intraperitoneal injection of 5 IU of Pregnant mare serum gonadotropin (PMSG) followed by 5 IU of hCG 48 h later) significantly reduced the density and maturity of uNK cells in pregnant mice, suggesting an inhibitory effect of upregulated estrogen signaling on the accumulation and maturation of uNK cells [ 48 ]. Regarding NK function, Jaillon et al reported that pro-inflammatory cytokine production and NK cell activity increased after menopause, whereas estrogen therapy (0.625 mg conjugated estrogen + 2.5 mg medroxyprogesterone acetate for 2 months) could reverse this effect [ 49 , 50 ], indicating that estrogen may suppress peripheral NK cell activity and the secretion of pro-inflammatory cytokines.…”
Section: Regulation Of Estrogen On Differentiation Of Endometrial Nk ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of uNK cell recruitment, Chantakru, S, demonstrated that estrogen could enhance homing (ovariectomized C57Bl/6 mice, 17β-estradiol at 100 ng/day, 3 days) by upregulating the expression of L-selectin and α-integrin on circulatory CD56 bright NK cells [ 47 ]. Conversely, Ma, R et al found that estrogen stimulation (pseudopregnant CD1 mice obtained blastocysts transfer, intraperitoneal injection of 5 IU of Pregnant mare serum gonadotropin (PMSG) followed by 5 IU of hCG 48 h later) significantly reduced the density and maturity of uNK cells in pregnant mice, suggesting an inhibitory effect of upregulated estrogen signaling on the accumulation and maturation of uNK cells [ 48 ]. Regarding NK function, Jaillon et al reported that pro-inflammatory cytokine production and NK cell activity increased after menopause, whereas estrogen therapy (0.625 mg conjugated estrogen + 2.5 mg medroxyprogesterone acetate for 2 months) could reverse this effect [ 49 , 50 ], indicating that estrogen may suppress peripheral NK cell activity and the secretion of pro-inflammatory cytokines.…”
Section: Regulation Of Estrogen On Differentiation Of Endometrial Nk ...mentioning
confidence: 99%
“…Estrogen was also reported to increase the secretion of CCL2 in uNK cells (primary uNK cells, estrone 10 −8 mol/L or estradiol 10 −8 mol/L, cultured for 2 h), which is involved in the construction of blood vessels in the endometrium [ 53 ]. These conflicting findings on NK cell proliferation, recruitment, cytotoxicity, and cytokine secretion [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ] indicate that the influence of estrogen on NK cells may differ based on the cell type, the method of administration, and the duration of exposure to estrogen. This highlights the need for additional research to fully understand these complex interactions.…”
Section: Regulation Of Estrogen On Differentiation Of Endometrial Nk ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of the increased rate of placental disorders may involve endometrial changes associated with high estradiol levels. In our previous study, we found that OS resulting in aberrant estrogen signaling could lead to disorders in uNK cells, which are crucial for placentation [ 10 ]. In addition, the potential effects of high estradiol levels on oocytes during OS must be considered.…”
Section: Introductionmentioning
confidence: 99%